2017
DOI: 10.1111/nph.14648
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of two half‐size ABC transporter genes in aluminium‐accumulating buckwheat

Abstract: Buckwheat (Fagopyrum esculentum Moench) is able to detoxify high aluminium (Al) internally by sequestering it to the vacuoles in the leaves; however, the molecular mechanisms underlying this sequestration are unknown. We performed proteomic analysis with the leaf tonoplast-rich fraction and identified two half-size ABC transporters; FeASL1.1 and FeALS1.2. We investigated the gene expression patterns and subcellular localization. To demonstrate their physiological role, we expressed FeALS1.1 or FeALS1.2 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In the buckwheat root tip, we identified a gene encoding FeALS1 and a gene encoding FeIREG1, which is consistent with a previous report [ 17 , 20 ]. Very recently, based on the proteomic analysis of a tonoplast-rich fraction, Lei et al identified two FeALS1 proteins—FeALS1.1 and FeALS1.2—from buckwheat leaves, and demonstrated their function as tonoplast-localized transporters for Al sequestration into vacuoles [ 40 ]. While the expression of FeALS1.1 was induced by Al both in the roots and shoots, FeALS1.2 was constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In the buckwheat root tip, we identified a gene encoding FeALS1 and a gene encoding FeIREG1, which is consistent with a previous report [ 17 , 20 ]. Very recently, based on the proteomic analysis of a tonoplast-rich fraction, Lei et al identified two FeALS1 proteins—FeALS1.1 and FeALS1.2—from buckwheat leaves, and demonstrated their function as tonoplast-localized transporters for Al sequestration into vacuoles [ 40 ]. While the expression of FeALS1.1 was induced by Al both in the roots and shoots, FeALS1.2 was constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in buckwheat ( Fagopyrum esculentum Moench), internal detoxification of Al is achieved by Al-oxalate and this complex was sequestrated in the vacuoles of the leaves [ 22 , 23 , 24 , 25 ]. Two genes from buckwheat, FeALS1.1 and FeALS1.2 , which belong to the half-size ABC transporter genes, were found to play a role in the internal detoxification of Al [ 26 ]. For external detoxification, plant root apexes exudate organic acids to chelate Al in the rhizosphere [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, protein-protein and DNA-protein interactions in plant cells have been examined in a high-throughput manner Kato 2007, Wehner et al 2011). In buckwheat, methods for protoplast isolation and transient gene expression have been reported previously, but have not been optimized for a high-throughput platform (Lei et al 2017a, 2017b, Shen et al 2002.…”
Section: Introductionmentioning
confidence: 99%